What Is Gender Equality in Science?. (May 2019) - O'Brien, Katherine R.; Holmgren, Milena; Fitzsimmons, Terrance; Crane, Margaret E.; Maxwell, Paul; Head, Brian
Abstract : Why do inequalities persist between male and female scientists, when the causes are well-researched and widely condemned? In part, because equality has many dimensions. Presenting eight definitions of gender equality, we show each is important but incomplete. Rigid application of any single equality indicator can therefore have perverse outcomes.